The Third Prize of the 9th Composition Competition of Group A2 MUSICACOUSTICA-BEIJING, October 2012 - Hasnizam, Abd Wahid (Universiti Malaysia Sarawak, 2012)
Hasnizam Abd Wahid, "Mikro" is honoured as The Third Prize of the 9th Composition Competition of Group A2 MUSICACOUSTICA-BEIJING, 2012 Organizing committee of MUSICACOUSTICA-BEIJING, October 2012